Metalloproteins Methods and Protocols - Fontecilla-Camps, Juan C.; Fontecilla-Camps, Juan C.; Nicolet, Yvain.; Nicolet, Yvain. (Methods in Molecular Biology, 2014)
Metalloproteins are involved in many key biological processes such as gas transport and metabolism, photosynthesis, cell respiration, the Krebs cycle and many other vital redox reactions. Metalloproteins: Methods and Protocols addresses multiple aspects of metalloenzyme research from the production and purification of metalloproteins using both standard recombinant techniques and a cell-free system, to the electrochemical analysis of metalloproteins, as well as IR techniques, Mössbauer spectroscopy and the theoretical interpretation of metalloenzyme catalytic and redox processes, to name a few topics. Written in the successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible protocols, and notes on troubleshooting and avoiding known pitfalls. Authoritative and easily accessible, Metalloproteins: Methods and Protocols seeks to serve both professionals and novices interested in the metalloprotein field.